Using QM/MM Methods for the Exploration of Electron Transfer Pathways - Lucas, Maria (2012)
Many proteins are known for their ability to perform several functions such as oxidation/reduction, gas transport or storage and electron transfer depending on the active site´s environment or on the available ligands. Consequently, the interest in an atomic (and electronic) description of these functions´ mechanism is very high. However, obtaining such detailed information is not a trivial task. The continued growth of computer power and the development of theoretical techniques, such as mixed quantum mechanics and molecular mechanics, permit the atomistic study of complex biological systems. Here, recent computational advances in protein electron transfer studies on our group are reviewed. We centered our attention on long distance electron transfer processes and the application of the QM/MM e-pathway method to protein systems.